ON A QUESTION OF A. SOZUTOV - Mirzakhanyan, N.E.; Piliposyan, H.V. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2018)
In the paper an answer to a problem posed by A.I. Sozutov in the Kourovka Notebook is given. The solution is based on some modification of the method that was proposed for constructing a non-abelian analogue of the additive group of rational numbers, i.e. a group whose center is an infinite cyclic group and any two non-trivial subgroups of which have a non-trivial intersection.